Decades of monitoring have informed the stewardship and ecological understanding of Australia's Great Barrier Reef. (December 2020) - Emslie, Michael J.; Bray, Peran; Cheal, Alistair J.; Johns, Kerryn A.; Osborne, Kate; Sinclair-Taylor, Tane; Thompson, Cassandra A.
Abstract: Australia's Great Barrier Reef is an iconic ecosystem that has been managed using a multi-use zoning plan over the last four decades. The Long-Term Monitoring Program (LTMP) of the Australian Institute of Marine Science (AIMS) is one of the world's longest running and most comprehensive coral reef monitoring programs, having documented the status and trends of Great Barrier Reef coral and reef fish assemblages over the last 32 years. The LTMP uses standard operating procedures to determine reef condition: broad-scale manta tow surveys of entire reef perimeters combined with intensive SCUBA surveys at permanently marked sites. This unique dataset has provided critical and reliable information about the status of the Great Barrier Reef by: defining and tracking spatio-temporal patterns in the distribution and abundance of fish and benthic assemblages; documenting disturbance regimes and their impacts upon reef status; and demonstrating the conservation benefits of the implementation and expansion of no-take marine reserves within the Marine Park. The long-term dataset, which is publicly available, has also been widely used to address fundamental ecological questions. Examples of key studies include: the role of herbivorous fishes in preventing phase shifts on coral reefs, and how heat stress has delayed coral recovery. Information from the LTMP directly informs management agencies about the status and trends of reef health through regular web-based reporting, direct consultation, peer-reviewed papers, conference presentations and provision of information for the five-yearly Outlook Report produced by the Great Barrier Reef Marine Park Authority for the Australian Government. Highlights: The LTMP has demonstrated the conservation benefits of large networks of no-take marine reserves. LTMP data revealed increased resilience of coral reef assemblages to acute disturbances inside no-take marine reserves. LTMP documented a loss of 50% of hard coral cover across the Great Barrier Reef (GBR) from the mid-1980s until 2012. Phase shifts from coral dominated to algal dominated benthic communities are relatively rare on the GBR. Thermal stress can slow coral recovery.